Periodontal hemodynamics state in the stabilization stage when applied standard, and declared tires on the background of active orthopedic treatment - Ищенко, П. В.; Борисенко, А. В. (Actual Dentistry, 2020)
Relevance. Any orthopedic treatment is an increased load on periodontal tissue. In the presence of compensated changes, such an additional load may exceed the available capabilities of periodontal tissues and cause an exacerbation of an undesirable pathological process. The use of orthopedic appliances in this case and the duration of their action are some of the complex and pressing problems in dentistry. Purpose of the study. To study the state of hemodynamics when applying declared and well-known tires in their area of responsibility in patients with periodontal stabilization and various types of occlusion. Materials and methods. In the studied groups with pathology of the bite (bipognathia, progenia, deep bite) and a stabilized periodontal period, there were 30 people groups with the claimed test tires. And groups with well-known traditional tires, with the same number of people in three groups. In the study of the claimed tires, fixed structures for dentitions without defects were used: the interdental splint for the entire dentition, and if the teeth were depulped, then the interdental splint for the entire dentition for depulpted teeth. Tires differed only in fixing method. In the study of traditional tires, designs for dentition without defects were also used: cap and crown tires. Results. A study of periodontal hemodynamics showed that it is almost completely restored during orthopedic treatment. The microcirculation index and diagnostically valuable indices are approaching normal values. It is noted that even complete orthopedic splinting with traditional tires does not lead to normalization of blood circulation in periodontal tissues with occlusion pathology. Conclusions. The use of orthopedic therapy has shown its high efficiency, which allows us to recommend the use of complex therapy for the recurrent course of chronic periodontal diseases in orthopedic patients in order to increase the effectiveness of treatment and rehabilitation of this group of patients. Key words: generalized periodontitis in the stabilization stage, fixed constructions of dental tires, microcirculation state.